Taxonomic study of the leafhopper genus Arboridia from China (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) - Zou, Hongfen; Zhang, Yalin (Zootaxa, 2026)
Species of the genus Arboridia Zachvatkin from China are reviewed, with nine new species described in the nominate subgenus Arboridia: A. (Arboridia) anceps, A. (A.) cuihuashanastra, A. (A.) fluctiformis, A. (A.) longiora, A. (A.) medialis, A. (A.) orbicularis, A. (A.) procurva, A. (A.) tenuicava, and A. (A.) wanshuigouensis spp. nov. One new combination is proposed: A. (A.) cambera (Song & Li, 2016) comb. nov. In addition, two species are newly recorded from China: A. (A.) padi and A. (A.) silvarum. Detailed morphological descriptions and illustrations of these species, along with a checklist of all known species from China are provided.